Christianity and Humanitarianism in the Doukhobor Campaign, 1895–1902. (2nd July 2016) - Kelly, Luke
Abstract: This article examines the campaign undertaken by British Quakers in the 1890s to defend the Doukhobor sect of Russian Christians. The notion of humanitarian sympathy is too often applied as if it were a constant. Quakers are seen by many as exemplars of humanitarian action. By contrast this article argues that the concern that led to defend the Doukhobors came from very specific images of Christian suffering, and that the campaign to defend the sect was shaped by religious, not humanitarian, aims and methods and the particular history and repertoire of Quaker campaigning. It contributes to the history of humanitarianism by showing how humanitarian campaigning derives from the social and cultural history of various actors, and how humanitarian activity is coloured, at all levels, by its social and ideological positioning.